Virtual Phacoemulsification Surgical Simulation Using Visual Guidance And Performance Parameters As A Feasible Proficiency Assessment Tool - Sundaraj, Kenneth; Sulaiman, Mohd Nazri; A. Qamarruddin, Fazilawati; Chee, Kiang Lam (BioMed Central Ltd., 2016)
Background: Computer based surgical training is believed to be capable of providing a controlled virtual environment for medical professionals to conduct standardized training or new experimental procedures on virtual human body parts,which are generated and visualised three-dimensionally on a digital display unit. The main objective of this study was to conduct virtual phacoemulsification cataract surgery to compare performance by users with different proficiency on a virtual reality platform equipped with a visual guidance system and a set of performance parameters.Methods: Ten experienced ophthalmologists and six medical residents were invited to perform the virtual surgery of the four main phacoemulsification cataract surgery procedures – 1) corneal incision (CI),2) capsulorhexis (C),3) phacoemulsification (P), and 4) intraocular lens implantation (IOL).Each participant was required to perform the complete phacoemulsification cataract surgery using the simulator for three consecutive trials (a standardized 30-min session).The performance of the participants during the three trials was supported using a visual guidance system and evaluated by referring to a set of parameters that was implemented in the performance evaluation system of the simulator.Results: Subjects with greater experience obtained significantly higher scores in all four main procedures – CI1 (ρ = 0.038),CI2 (ρ = 0.041),C1 (ρ = 0.032), P2 (ρ = 0.035) and IOL1 (ρ = 0.011).It was also found that experience improved the completion times in all modules – CI4 (ρ = 0.026),C4 (ρ = 0.018),P6 (ρ = 0.028) and IOL4 (ρ = 0.029).Positive correlation was observed between experience and anti-tremor – C2 (ρ = 0.026) P3 (ρ = 0.015),P4 (ρ = 0.042) and IOL2 (ρ = 0.048) and similarly with anti-rupture – CI3 (ρ = 0.013),C3 (ρ = 0.027),P5 (ρ = 0.021) and IOL3 (ρ = 0.041).No significant difference was observed between the groups with regards to P1 (ρ = 0.077). Conclusions: Statistical analysis of the results obtained from repetitive trials between two groups of users reveal that augmented virtual reality (VR) simulators have the potential and capability to be used as a feasible proficiency assessment tool for the complete four main procedures of phacoemulsification cataract surgery (ρ < 0.05),indicating the construct validity of the modules simulated with augmented visual guidance and assessed through performance parameters.